PENGARUH PELVIC TILTING TERHADAP PENURUNAN SKALA NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER 2 DI KLATEN JAWA TENGAH - Ferina Ratnasari, NIM011511223010 (2017)
Background: Low back pain on pregnancy is inconvenience problem often complained by pregnant women. Back pain experienced during pregnancy had impact for women daily activity. Pelvic titling was non pharmacological management expected to reduce lower back pain. Therefore we conducted a study to know influence pelvic titling to reduce lower back pain scale for pregnant women on second trimester. Method: Method of the research was one group pre-test and post test design. Sample used 31 pregnant women on second trimester who complained low back pain. They intervened with pelvic titling movement as much 9x during 3 weeks. Result: The results of Wilxocon Sign Rank Test of 31 pregnant women who complained of back pain before pelvic tilting resulted in 14 (45.2%) respondents entered the category rather sick and 17 (54.8%) of respondents entered the pain category on measuring the scale of back pain with Using a Nordic Body Map questionnaire. After 9 weeks pelvic tilting was given for 3 weeks, it was concluded that the decrease of lower back pain scale 11 respondents (35.5%) decreased the lower back pain category, and 20 respondents (64.5%) decreased the scale Lower back pain category no pain, with the value of P 0.001 with α = 0.005 then P <α. Conclusion: Pelvic tilting exercises have an effect on reducing the scale of low back pain in pregnant women trimester 2. Trimester 2 pregnant women who complain of back pain is expected to run pelvic tilting exercise program with the supervision of midwives or doctors.